MAQASID PERSPECTIVE ON THE MEANING OF POVERTY IN LEGAL AID: Study of Poverty as a Threat to Human Security - Sabil, Jabbar; Muda Rianto, Arief (Program Studi Hukum Ekonomi Syariah Fakultas Syariah dan Hukum UIN Ar-Raniry, 2023)
The government provides legal assistance to poor people in the context of access to justice. Unfortunately, the meaning of poverty in legal aid is often limited to being poor in assets, resulting in partiality that sacrifices the values ​​of justice. This problem inspired the author to research the meaning of poverty in legal aid through a maqasid sharia perspective. The author asks two questions: 1) what is the nature of poverty in legal aid? 2) what is the maqasid Sharia perspective on poverty in legal aid? This research concludes that being poor in legal aid should be interpreted as being poor in spirit (faqīr al-qalb). In dealing with mentally poor people, legal practitioners must have holistic analytical skills and see poverty as part of the social system and legal system. This conclusion supports each other with other sharia maqasid to increase the quantity and quality of legal practitioners.